Penyuluhan Terapi Herbal untuk Mengontrol Tekanan Darah pada Lansia dengan Hipertensi - Adhin Al Kasanah; Priyoto Priyoto; Binar Wahyuning Widhi (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a disease whose prevalence continues to increase and occurs frequently in the elderly. The severity of hypertension is often linked to non-adherence to medication consumption. The objective of this community service activity is to improve the knowledge and skills of the elderly and their caregivers regarding the use of herbal therapy as a reliable and effective complementary treatment for controlling blood pressure. The activity was conducted through health education and practical demonstrations involving 29 participants. The main instrument that used in the health education was a leaflet. The results of the pre- and post-activity assessment showed an average increase in knowledge scores regarding herbal therapy for blood pressure control. In conclusion, this community service activity successfully enhanced the health literacy and practical skills of the elderly in utilizing evidence-based herbal therapy to lower blood pressure. Further effort is needed to achieve comprehensive and self-managed blood pressure control in elderly.